The Semantics and Ontology of The Average American. (16th May 2017) - Collins, John
Abstract: The received wisdom is that truth-conditional semantics presupposes and entails certain externalist ontological commitments. The idea is simple enough: if a semantic theory specifies (compositional) truth conditions, then, for any given sentence that is true, the theory will specify the very conditions that hold such that the sentence is true. Presumably, such conditions are exactly ways the world might be that make our truths true and our falsehoods false. Semantics is world-involving merely by dint of being truth-involving. A general worry for this picture, no matter how otherwise tempting it might be, is the occurrence of referentially defective words and expressions, ones that appear properly to contribute to the truth conditions of sentences that may be variously true or false but which do not appear to have referents we should otherwise sanction. Chomsky and others have claimed that, far from being outliers, a class of peculiar cases, referentially defective expressions are the absolute norm, utterly ubiquitous. The focus of the following will be the apparently referentially defective expression the average American . I shall first spell out the problem it poses and upon that basis suggest a general two-tier approach to natural language semantics, under which the interpretation of syntax (the first tier) is not world-involving, but another level of interpretation is; this second tier of interpretation, however, is not specifically linguistic. Secondly, the most thorough analysis of 'the average+N' kind of construction will be presented due to Kennedy and Stanley (2009), whose aim is to defend the orthodoxy; that is, such an expression may be given a clear semantic analysis that renders it non-defective. Thirdly, a number of severe problems for the analysis will be presented. Fourthly, an alternative account of the peculiar properties of the construction will be offered in line with the two-tier proposal previously suggested. The account preserves the defectiveness of the average American, but renders it unproblematic from a theoretical perspective.